Bangsamoro separatism and classical counterinsurgency: reconsidering revolutionary war in the southern Philippines - Bukit, Mathew L. (2022)
The dominant history of Muslim armed separatism in the Philippines obscures the insurgency’s character. Insurgents espouse revolutionary war, even though this mischaracterizes the interests constituted in the insurgent cause. Patricio Abinales’ critiques of the orthodoxy are applied to disambiguate the Bangsamoro cause, highlighting the insurgency’s concurrent supralocal and local logics. Supralocal-local dissonance is reconciled by recasting the Bangsamoro cause as a supralocal-local bargain through Stathis Kalyvas’ concept of alliance, retaining classical counterinsurgency theory’s macropolitical locus but imbued with cognizance of the insurgency’s micropolitics. This approach challenges the perceived finality of the insurgency after the Bangsamoro Autonomous Region in Muslim Mindanao.